Reconstruction of John B. Watson's Behaviorism Principle in Indonesia's Education System in The Digital Age - Latiafatuz Zahra; Asiana Asiana; Muhammad Sirozi (Journal of Educational Sciences, 2026)
This research reconstructs the core principles of John B. Watson’s behaviorism in the context of Indonesia’s educational system during the digital age. Modern education necessitates adaptability to technological advancements, prompting a reevaluation of traditional learning theories. The objective of this study is to investigate the relevance of Watson’s psychological behaviorism in relation to contemporary digital learning and to assess its implementation in current teaching methodologies. Employing a qualitative library research approach, the study references a diverse range of literature, including books, journals, and research papers pertinent to behaviorism and educational technology. The results indicate that behaviorism, which focuses on stimulus–response interactions and reinforcement, continues to be effective for structured and quantifiable learning processes, thereby facilitating adaptive digital instruction. Nevertheless, it also uncovers certain limitations, such as a decrease in student creativity and an overreliance on external motivation. The study concludes that while behaviorism provides systematic and observable learning advantages, it should be combined with constructivist and humanistic theories to more effectively address emotional and cognitive aspects, ultimately improving learning outcomes within Indonesia’s digital education framework.